2018
DOI: 10.1111/resp.13339
|View full text |Cite
|
Sign up to set email alerts
|

Is the consumption of fast foods associated with asthma or other allergic diseases?

Abstract: The associations between the consumption of fast foods and asthma or allergic diseases have not been clarified. The aim of this study was to determine whether fast foods consumption is associated with asthma or allergic diseases. Databases were searched up to February 2018. Studies investigating the associations between fast foods consumption and asthma or allergic diseases were considered eligible. Included studies were assessed for quality using standardized critical appraisal checklists. The quality scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
2
19
0
1
Order By: Relevance
“…Several prior studies have found positive associations between processed or fried meat consumption and asthma, [52][53][54] and one recent systematic review found that hamburger consumption had a particularly strong association with asthma. 55 Our findings support a causal pathway whereby intestinal metabolites mediate at least part of the association between fried and processed meat consumption and asthma.…”
Section: Discussionsupporting
confidence: 69%
“…Several prior studies have found positive associations between processed or fried meat consumption and asthma, [52][53][54] and one recent systematic review found that hamburger consumption had a particularly strong association with asthma. 55 Our findings support a causal pathway whereby intestinal metabolites mediate at least part of the association between fried and processed meat consumption and asthma.…”
Section: Discussionsupporting
confidence: 69%
“…Over recent decades, the prevalence of asthma and allergic diseases has adequately increased to pose a public health concern [1-3]. Many studies have proposed that the increase in asthma and allergic diseases are attributed to changes in our diets [1,2], while others have linked it to environmental factors such as smoking, seasonal variations and air pollution [4][5][6]. A study conducted in children and adolescents in over 40 countries showed that up to 25% of children and nearly 40% of adolescents consume fast foods frequently [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that people living in developed countries have adopted a Westernized lifestyle [2]. This is a diet that mainly consists of fast foods and is rich in processed foods, fats and sugar.…”
Section: Introductionmentioning
confidence: 99%
“…Je mehr Fastfood, desto schlechter: Bei Konsumation von 3 oder mehr Fastfood-Mahlzeiten pro Woche zeigten sich signifikant vermehrt Rhinokonjunktivitis und Ekzem. Beim Vergleich der beiden Fastfood-Gruppen untereinander fand man in der Gruppe der ≥3 Hamburgers & Co-Esser eine signifikant erhöhte Wahrscheinlichkeit, an schwerem Asthma und schwerer Rhinokonjunktivitis zu leiden (Wang et al 2018b).…”
Section: Endogene Glykierungunclassified